Gender Disparities in Africa's Labor Market - Arbache, Jorge Saba; Kolev, Alexandre; Filipiak, Ewa (World Bank, 2012)
The main aim of this book is to help fill the gap in current knowledge about the nature, the extent, and some of the root causes of gender disparities in Africa, showing what can be revealed about the application of standard and less standard tools and methods to existing survey and national account data. The analysis herein is novel in providing in-depth assessments of some of the sources of gender disparities in different labor market outcomes. A part of the book provides results on the basis that data are as comparable as possible for 18 countries. These results were extracted from multi-topic, integrated household surveys conducted in Africa around 2000 and thus may not represent the latest trends, but they have the merit to be comparable. The cross-national perspective provides a benchmark against which other results for individual countries and more recent data presented here may be compared. Additional goals are to demonstrate the possibilities, as well as the challenges, of analysis of gender inequality in labor market outcomes with existing survey data, to support the improvement of data collection, and to stimulate further research on gender disparities in Africa. The book touches on policy issues at various points, although it is not principally a book about using policy to reduce gender inequality. Rather, it aims to provide analysis that is relevant to policy design.